2017
DOI: 10.1111/hojo.12232
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanics of Reform: Implementing Correctional Programmes in English Prisons

Abstract: Delivering correctional programmes in the prison environment has proved challenging, and desired outcomes have not always been achieved. Drawing on interview data, this article considers the mechanics through which programmes are introduced into English prisons and how the environment shapes what is accomplished. We argue that the operation of programmes is influenced by institutional features (such as values, priorities and resources), situational features (such as the challenges posed by operating in the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 42 publications
0
12
1
1
Order By: Relevance
“…Ireland et al (2016) evaluated the cognitive skills programme of male prisoners in the UK prisons and highlighted that cognitive skills programmes may be best considered as precursors to longer term therapies, whereas activities should focus on improvement and not recovery. Bullock et al (2018) recently argued that the outcomes of prison-based correctional programmes have often fallen short of expectations, and the programmes are shaped by features of the organisational environment and how they interact with programme processes and staff. Further, authors indicated that the "what works" movement was propelled by findings from studies which demonstrated that well-designed programmes, especially those based on cognitive behavioural therapy (CBT), could produce reductions in reconviction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Ireland et al (2016) evaluated the cognitive skills programme of male prisoners in the UK prisons and highlighted that cognitive skills programmes may be best considered as precursors to longer term therapies, whereas activities should focus on improvement and not recovery. Bullock et al (2018) recently argued that the outcomes of prison-based correctional programmes have often fallen short of expectations, and the programmes are shaped by features of the organisational environment and how they interact with programme processes and staff. Further, authors indicated that the "what works" movement was propelled by findings from studies which demonstrated that well-designed programmes, especially those based on cognitive behavioural therapy (CBT), could produce reductions in reconviction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the issues in the constant argument over rehabilitations is that the prior studies have drawn very little attention on systematic empirical knowledge about the success or failure of rehabilitation programmes with different recreational activities and in different institutional settings. Further, prior studies were not well enough to focus prisoners' motivations to select their vocational training, how the organisational context of individual prisoners interacts with that govern programmes or their attitudes about their work or training (Bullock et al, 2018). Thus, this study contributes to the growing body of research with an evaluation of the rehabilitation programme that is offered in Sri Lankan prisons.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…While, as noted, prison-based OMPs can be effective, there has also been disappointment about what they have achieved (Hollin et al, 2004, Maguire et al, 2010). A range of implementation problems, such as resourcing and recruiting suitable staff, have negatively affected what has been achieved (Burdon et al, 2002; Harper and Chitty, 2005; Lin, 2002; Maguire, 2004), and establishing and sustaining OMPs in closed institutions is far from straightforward (Bullock et al, 2018; Lin, 2002). Prisons have also struggled to proactively respond to needs assessments and embed throughcare (CJJI, 2017; HMIPP, 2013, 2017; Maguire and Raynor, 2017).…”
Section: The Position Of Rehabilitation In Penal Policy and Practicementioning
confidence: 99%